Attenuating Photostress and Glare Disability in Pseudophakic Patients through the Addition of a Short-Wave Absorbing Filter - Billy R. Hammond (Journal of Ophthalmology)
To evaluate the effects of filtering short wavelength light on visual performance under intense light conditions among pseudophakic patients previously implanted with a clear intraocular lens (IOL). This was a patient-masked, randomized crossover study conducted at 6 clinical sites in the United States between September 2013 and January 2014. One hundred fifty-four bilaterally pseudophakic patients were recruited. Photostress recovery time and glare disability thresholds were measured with clip-on blue-light-filtering and placebo (clear; no blue-light filtration) glasses worn over patients’ habitual correction. Photostress recovery time was quantified as the time necessary to regain sight of a grating target after intense light exposure. Glare disability threshold was assessed as the intensity of a white-light annulus necessary to obscure a central target. The order of filter used and test eye were randomized across patients. Photostress recovery time and glare disability thresholds were significantly improved (both P<0.0001) when patients used blue-light-filtering glasses compared with clear, nonfiltering glasses. Compared with a nonfiltering placebo, adding a clip-on blue-absorbing filter to the glasses of pseudophakic patients implanted with clear IOLs significantly increased their ability to cope with glare and to recover normal viewing after an intensive photostress. This result implies that IOL designs with blue-light-filtering characteristics may be beneficial under intense light conditions.